Elite synchronized swimmers display decreased energy availability during intensified training - Schaal, K.; Tiollier, E.; Le Meur, Y.; Casazza, G.; Hausswirth, C. (Scandinavian Journal of Medicine & Science in Sports, 2017)
Elite synchronized swimmers follow high-volume training regimen that result in elevated rates of exercise energy expenditure (ExEE). While adequate energy intake (EI) is important to optimize recovery, a number of sport-specific constraints may lead to chronically low energy availability (EA = EI-ExEE). This study aimed to quantify changes in EA, endocrine markers of energy conservation, and perceived fatigue in synchronized swimmers, during a week of baseline training followed by 4 weeks of intensified training (IT). EI, ExEE, and body composition were measured in nine swimmers at Baseline, midpoint (ITWK2), and end of IT (ITWK4). Waking saliva samples were obtained to measure [leptin]s, [ghrelin]s, and [cortisol]s. Fatigue ratings were provided daily. ExEE increased by 27% during IT. Swimmers increased EI from Baseline to ITWK2, but decreased it significantly from ITWK2 to ITWK4. EA, fat mass, and [leptin]s decreased from Baseline to ITWK4, while [ghrelin]s increased significantly. Fatigue at ITWK4 was inversely correlated with Baseline EI and EA. The significant decrease in EA was accompanied by endocrine signs of energy conservation in elite swimmers. As perceived fatigue was associated with low EA, particular attention should be paid to these athletes' energy intake during phases of heavy training.